Four additional mouse crosses improve the lipid QTL landscape and identify Lipg as a QTL gene[S] - Zhiguang Su; Naoki Ishimori; Yaoyu Chen; Edward H. Leiter; Gary A. Churchill; Beverly Paigen; Ioannis M. Stylianou (Journal of Lipid Research, 2009)
To identify genes controlling plasma HDL and triglyceride levels, quantitative trait locus (QTL) analysis was performed in one backcross, (NZO/H1Lt × NON/LtJ) × NON/LtJ, and three intercrosses, C57BL/6J × DBA/2J, C57BL/6J × C3H/HeJ, and NZB/B1NJ × NZW/LacJ. HDL concentrations were affected by 25 QTL distributed on most chromosomes (Chrs); those on Chrs 1, 8, 12, and 16 were newly identified, and the remainder were replications of previously identified QTL. Triglyceride concentrations were controlled by nine loci; those on Chrs 1, 2, 3, 7, 16, and 18 were newly identified QTL, and the remainder were replications. Combining mouse crosses with haplotype analysis for the HDL QTL on Chr 18 reduced the list of candidates to six genes. Further expression analysis, sequencing, and quantitative complementation testing of these six genes identified Lipg as the HDL QTL gene on distal Chr 18. The data from these crosses further increase the ability to perform haplotype analyses that can lead to the identification of causal lipid genes.